Age-period-cohort analysis of syphilis epidemics in Eastern China, China, 2005–2024 - Zheyuan Ding; Shuangqing Wang; Junjie Li; Haocheng Wu; Qinbao Lu; Xinyi Wang; Tianyin Fu; Kui Liu; Chen Wu (Frontiers in Public Health)
BackgroundSyphilis remains one of the serious public health challenges in China and worldwide. This study aims to assess the potential independent risks associated with age, period, and birth cohort for the reported incidence of syphilis in Eastern China.MethodsData on all syphilis cases from 2005 to 2024 in Zhejiang Province in Eastern China were collected from the China Information System for Disease Control and Prevention. The Age-Period-Cohort (APC) model was used to analyze the effect coefficients, which were then converted into relative risks (RRs).ResultsFrom 2005 to 2024, a total of 617,097 syphilis cases were reported in Zhejiang Province. The reported incidence of syphilis decreased by an average of −3.53% per year across all age groups (95% CI: −4.34, −2.70%). The age effect showed that the highest reported incidence was among individuals aged 20–24 years, with a relatively high rate also observed in those aged 60 years and above. The period effect indicated that compared with the reference group of 2010–2014 with the highest reported incidence risk, the risk in 2020–2024 was the lowest (RR = 0.48; 95% CI: 0.43, 0.54). The cohort effect shows that the risk decreased in later birth cohorts, with the highest reported incidence risk in the birth cohort of 1960–1964 (RR = 1.30; 95% CI: 1.08, 1.57) and the lowest risk in the birth cohort of 2020–2024 (RR = 0.00; 95% CI: 0.00, 0.18).ConclusionThe reported incidence of syphilis in Zhejiang Province has shown an overall downward trend. The implementation of national syphilis control programs has achieved significant results. There is a need to strengthen the management of late-stage syphilis among older adults and enhance syphilis prevention and control efforts among adolescents.